EFFECT ON GROWTH AND YIELD OF POTATO (SOLANUM TUBEROSUM L.) VAR. KUFRI JYOTI BY NITROGEN INTEGRATION WITH DIFFERENT ORGANIC SOURCES AND ITS AFTER EFFECT ON SOIL - ANJU KEISHAM,; PUNABATI HEISNAM,; ABHINASH MOIRANGTHEM,; TAPAS DAS,; N. INDRAKUMAR SINGH,; L. NABACHANDRA SINGH, (The Bioscan, 2015)
An experiment was conducted at the Research Farm, College of Agriculture, Central Agricultural University, Imphal during rabi season to study the effect of nitrogen integration through different sources i.e. FYM, vermicompost and urea at different levels of substitution i.e., 25%, 50%, 75% and 100% to the recommended dose (RD) of nitrogen as urea by the organic sources. Supplementation of 75% RD of nitrogen from Urea i.e. 130 kg/ha and 25% RD of nitrogen from FYM i.e. 4 t/ha exhibited the highest growth, yield attributes and yield, net return per rupee investment and cost benefit ratio. Though the performance of the same level of substitution by vermicompost was next to FYM, it was not economical. While use of 100% RD of nitrogen from FYM i.e. 16 t/ha left higher residual available N and K and use of 50% RD of nitrogen from FYM i.e. 8 t/ha left higher residual P as compared to integration of chemical fertilizers with organic manures. However with the increase in level of FYM in integration the amount of residual nutrient in soil was also increased.